PENGARUH LINGKUNGAN SEKOLAH DAN KEDISIPLINAN BELAJAR TERHADAP MOTIVASI BELAJAR SISWA SMA NEGERI 7 KOTA KEDIRI - Rahayu, Diah Dwi; Irmayanti, Elis; Afandi, Tjetep Yusuf (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research is motivated  the problem of student learning motivati. It is clear that learning motivation has a positive effect on student outcomes and achievement in learning. Based on observations made at SMA Negeri 7 Kediri City during the New Normal period and the recovery period from distance learning (online) face-to-face. The results of talking with several students showed that students' motivation to learn was still low due to several environmental conditions, and student discipline who were still starting readjust to school. This study aims to determine the effect of decreasing student motivation in SMA Negeri 7 Kediri. From the results of this study are (1) the school environment has no effect on learning motivation with a significant value of 0.066 > 0.05. (2) Learning discipline has an effect on learning motivation, as shown by the value obtained 0.002 <0.05. (3) The school environment and discipline affect students' learning motivation, as evidenced by the simultaneous test obtained sig = 0.000 <0.05, meaning that it has a positive effect on student learning outcomes at SMA Negeri 7 Kediri. And indicated by the value of the coefficient of determination (R Square) of = 0.499 = 50%, meaning that it is classified as moderate.